Gaps in Receipt of Regular Eye Exams among Medicare Beneficiaries Diagnosed with Diabetes or Chronic Eye Diseases - Sloan, Frank A (Ophthalmology, 2014)
OBJECTIVE: To examine a wide range of factors associated with regular eye exam receipt among elderly individuals diagnosed with glaucoma, age-related macular degeneration, or diabetes mellitus (DM). DESIGN: Retrospective analysis of Medicare claims linked to survey data from the Health and Retirement Study (HRS). PARTICIPANTS: The sample consisted of 2,151 Medicare beneficiaries who responded to the HRS. METHODS: Medicare beneficiaries with at least 1 of the 3 study diagnoses were identified by diagnosis codes and merged with survey information. The same individuals were followed over 5 years divided into 4 15-month periods. Predictors of the number of periods with an eye exam evaluated were beneficiary demographic characteristics, income, health, cognitive, and physical function, health behaviors, subjective beliefs about longevity, the length of the individual’s financial planning horizon, supplemental health insurance coverage, eye disease diagnoses and low vision/blindness at baseline. We performed logit analysis of the number of 15-month periods in which beneficiaries received an eye exam. MAIN OUTCOME MEASURES: The primary outcome measure was the number of 15-month periods with an eye examination. RESULTS: Only one third of beneficiaries with the study’s chronic diseases saw an eye care provider in all 4 follow-up periods despite having Medicare. A quarter only obtained an eye exam at most during 1 of the 4 15-month follow-up periods. Among the 3 groups of patients studied, utilization was particularly low for persons with diagnosed DM and no eye complications. Age, marriage, education and a higher score on the Charlson index were associated with more periods with an eye exam. Male gender, being limited in Instrumental Activities of Daily Living at baseline, distance to the nearest ophthalmologist, and low cognitive function were associated with a reduction in frequency of eye exams. CONCLUSIONS: Rates of eye exams for elderly persons with DM or frequently occurring eye diseases, especially for DM, remain far below recommended levels in a nationally representative sample of persons with health insurance coverage. Several factors, including limited physical and cognitive function, and greater distance to an ophthalmologist, but not health insurance coverage, account for variation in regular use.